Integrating gender into index-based agricultural insurance: a focus on South Africa. Issue 4 (19th May 2019) - Born, Lorna; Spillane, Charles; Murray, Una
ABSTRACT: Index insurance is an agricultural risk management tool that can provide a safety net for smallholder farmers experiencing climate risk. While uptake and scale-out of index insurance may be slow among smallholders, we can learn from experiences that demonstrate where crop insurance can protect smallholders' livelihoods from climate risk. Integrating gender into climate risk management is necessary to ensure that the benefits of index insurance are experienced by both men and women. A dedicated intention to integrate gender may be required. Taking South Africa as a case study, the potential for gender-sensitive index insurance scale-out among smallholders is investigated.